Synthesis of 7-Hydroxy-4-methylcoumarin Using Polyaniline/Montmorillonite K10 Composite as Catalyst - Kolancilar, Hakan (Asian Journal of Chemistry, 2010)
The polyaniline/montmorillonite K10 composite consisting of conducting polyaniline and montmorillonite K10 was synthesized by the intercalation. The insertion of polyaniline between the interlayer of the clay was observed by means of IR spectroscopy. The composite was used as catalyst in Pechmann reaction. The advantages of the composite are ease of preparation, recovery and simple work-up.